ATP inhibits nuclear and mitochondrial type I topoisomerases from human leukemia cells. - Castora, F J (1986)
Type I topoisomerases have been purified from nuclei and mitochondria of human acute lymphoblastic leukemia cells. Both of these ATP-independent enzymes are actually found to be inhibited by ATP at physiologically significant concentrations. Other adenine nucleotides showed varying effects: ADP inhibited only at high concentrations; AMP had no effect on either topoisomerase. Both enzymes were also inhibited by dATP. The importance of the adenine ring structure was confirmed by the lack of an inhibitory effect observed with equivalent levels of GTP, UTP, CTP, or their deoxy counterparts. Assays performed in the presence of nonhydrolyzable analogs of ATP suggest that hydrolysis of ATP does not accompany this enzyme inhibition. This was supported by direct determination of the ATPase activity of the purified enzymes. Type I topoisomerase from calf thymus and HeLa cells were also found to be sensitive to ATP. These results suggest that mammalian type I topoisomerases in general may possess a nucleotide-binding site that may be involved in regulation of enzyme activity.